The Complete Chloroplast Genomes of Three Cardiocrinum (Liliaceae) Species: Comparative Genomic and Phylogenetic Analyses - Lu, Rui-Sen; Li, Pan; Qiu, Ying-Xiong (Frontiers in Plant Science, 2017)
The genus Cardiocrinum (Endlicher) Lindley (Liliaceae) comprises three herbaceous perennial species that are distributed in East Asian temperate-deciduous forests. Although all three Cardiocrinum species have horticultural and medical uses, studies related to species identification and molecular phylogenetic analysis of this genus have not been reported. Here, we report the complete chloroplast (cp) sequences of each Cardiocrinum species using Illumina paired-end sequencing technology. The cp genomes of C. giganteum, C. cathayanum and C. cordatum were found to be 152,653 bp, 152,415 bp, and 152,410 bp in length, respectively, including a pair of inverted repeat (IR) regions (26,364–26,500 bp) separated by a large single-copy (LSC) region (82,186–82,368 bp) and a small single-copy (SSC) region (17,309–17,344 bp). Each cp genome contained the same 112 unique genes consisting of 30 transfer RNA genes, 4 ribosomal RNA genes, and 78 protein-coding genes. Gene content, gene order, AT content, and IR/SC boundary structures were almost the same among the three Cardiocrinum cp genomes, yet their lengths varied due to contraction/expansion of the IR/SC borders. Simple sequence repeat (SSR) analysis further indicated the richest SSRs in these cp genomes to be A/T mononucleotides. A total of 45, 57, and 45 repeats were identified in C. giganteum, C. cathayanum and C. cordatum, respectively. Six cpDNA markers (rps19, rpoC2-rpoC1, trnS-psbZ, trnM-atpE, psaC-ndhE, ycf15-ycf1) with the percentage of variable sites higher than 0.95% were identified. Phylogenomic analyses of the complete cp genomes and 74 protein-coding genes strongly supported the monophyly of Cardiocrinum and a sister relationship between C. cathayanum and C. cordatum. The availability of these cp genomes provides valuable genetic information for further population genetics and phylogeography studies on Cardiocrinum.